XV Congress of the International Organization for Septuagint and Cognate Studies, Munich, 2013 - Kraus, Wolfgang, 1955-; Meer, Michaël N. van der; Meiser, Martin (Septuagint and cognate studies series, 2016)
"The study of Septuagint offers essential insights in ancient Judaism and its efforts to formulate Jewish identity within a non-Jewish surrounding culture. This book includes the papers given at the XV Congress of the International Organization for Septuagint and Cognate Studies (IOSCS), held in Munich, Germany, in 2013. The first part of this book deals with questions of textual criticism. The second part is dedicated to philology. The third part underlines the increasing importance of Torah in Jewish self-definition"--